RABBIT HOLE DAN PENINGKATAN LITERASI ANAK - Maryam, Siti; Mawadah, Sakinah (KOMUNIKA, 2018)
This article is the result of a study titled "Literature For Child Literacy Since Early: Case Studies Publish Rabbit Hole". The research was carried out on Rabbit Hole Publishers, a special publisher of children literature. The purpose of this first study was to find out the type and model of literature published by Rabbit Hole, the second is to know the role of Rabbit Hole in increasing the reading interest of Indonesian children. This research is limited to the role of Rabbit Hole in increasing the literacy of information only, and not discussing the widespread literasi. Pendekatan used is descriptive qualitative, and data obtained through interviews and observations, and supported by research literature and documentation. The results showed that the type of literature published by Rabbit Hole is a children's literature with several models such as pop-up books, touch-flavor books, book-open books that are all matched to the age of the child. The role of Rabbit Hole in improving reading interest in children is to bring a lot of information in every issue and inculcate good behaviors or habits such as minimizing the use of plastics in everyday life and so forth.